Functional Connectivity Magnetic Resonance Imaging Reveals Rapid and Reversible Changes in the Brain Following Induction of Psoriasiform Dermatitis in Mice. Issue 2 (April 2018) - Liu, Xiping; Imai, Yasutomo; Zhou, Yan; Yu, Sebastian; Li, Rupeng; Wu, Xuesong; Li, Shi-Jiang; Hwang, Sam T.
Functional connectivity magnetic resonance imaging (fcMRI), a specific form of MRI imaging, quantitatively assesses connectivity between brain regions that share functional properties. Functional connectivity magnetic resonance imaging has already provided unique insights into changes in the brain in patients with conditions such as depression and pain and symptoms that have been reported by patients with psoriasis and are known to impact quality of life. To identify the central neurological impact of psoriasiform inflammation of the skin, we applied fcMRI analysis to mice that had been topically treated with the Toll-like receptor agonist, imiquimod (IMQ) to induce psoriasiform dermatitis. Brain insula regions, due to their suggested role in stress, were chosen as seed regions for fcMRI analysis. Mouse ear and head skin developed psoriasiform epidermal thickening (up to 4-fold, P < .05) and dermal inflammation after 4 days of topical treatment with IMQ. After fcMRI analysis, IMQ-treated mice showed significantly increased insula fc with wide areas throughout the brain, including, but not limited to, the somatosensory cortex, anterior cingulate cortex, and caudate putamen ( P < .005). This reflects a potential central neurological impact of IMQ-induced psoriasis-like skin inflammation. These data indicate that fcMRI may be valuable tool to quantitatively assess the neurological impact of skin inflammation in patients with psoriasis.